2020
DOI: 10.1007/s00381-020-04695-3
|View full text |Cite
|
Sign up to set email alerts
|

Sturge-Weber syndrome: an update on the relevant issues for neurosurgeons

Abstract: Purpose Sturge-Weber syndrome (SWS) is a neurocutaneous facomatosis characterized by facial and leptomeningeal angioma, glaucoma, seizures, and neurological disability. Therefore, a challenging multidisciplinary interaction is required for its management. The goal of this paper is to review the main aspects of SWS and to present an illustrative pediatric series. Methods The pertinent literature has been analyzed, focused mainly on etiopathogenesis, pathology, clinical features, diagnostic tools, management, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(40 citation statements)
references
References 144 publications
1
38
0
1
Order By: Relevance
“…Indeed, the pathological specimens exhibit various cortical vascular abnormalities, such as venous hemangiomas in deep cortical layers, subcortical calcification of the vessel walls, and large jagged microcalcifications, among others [30]. Such abnormalities are similar to but not identical with those observed in Sturge-Weber syndrome, another condition with the possible coexistence of migraine and epilepsy [31].…”
Section: Imaging In Migraine and Celiac Diseasementioning
confidence: 95%
“…Indeed, the pathological specimens exhibit various cortical vascular abnormalities, such as venous hemangiomas in deep cortical layers, subcortical calcification of the vessel walls, and large jagged microcalcifications, among others [30]. Such abnormalities are similar to but not identical with those observed in Sturge-Weber syndrome, another condition with the possible coexistence of migraine and epilepsy [31].…”
Section: Imaging In Migraine and Celiac Diseasementioning
confidence: 95%
“…31,34 In cases of drug-resistant epilepsy, surgery should be considered, and early surgery should be pursued in order to reduce seizureinduced neuronal damage leading to cognitive decline and increase the chances of good postoperative neurological outcome. 16,29,[35][36][37] The decision for surgery is mostly based on the discussion and recommendation of a multidisciplinary team including pediatricians, pediatric neurosurgeons, pediatric neuroradiologists, and pediatric neurologists. 4 EEG findings usually correlate with the MRI findings, although, at times, radiologically noninvolved areas might show pathological changes on EEG as well.…”
Section: Seizure Control and Managementmentioning
confidence: 99%
“…4 The two main surgical approaches in SWS are lesionectomy and hemispherectomy. 4,36,37 To date, no consensus exists regarding the type of epilepsy surgery in SWS, and the chosen surgical approach is often dependent on the standard of the treating department and their experience. Generally, hemispherectomy is chosen in patients with a widespread or hemispheric defect, while focal lesionectomy can be selected if a clear focal seizure focus is seen, ideally correlating with the radiological location of the lesion as indicated by Wang et al 4 and Bourgeois et al 6 As shown in our meta-analysis, hemispherectomy was associated with a 100% rate of postoperative hemiparesis, and therefore it might be preferable at an early age since brain plasticity seems to be better in younger children, leading to potentially better outcomes in motor function.…”
Section: Seizure Control and Managementmentioning
confidence: 99%
“…[ 1 ] Sturge–Weber syndrome (SWS) is a sporadic syndrome, which is characterized by a triad of port-wine stain over the trigeminal nerve dermatome, choroidal vascular malformation of the eye and leptomeningeal angiomatosis. [ 2 ] This case emphasizes the importance of neurological and ophthalmic complications of SWS, which should be kept in mind by primary-care physicians when approaching a patient with nevus flammeus. So earlier evaluation of patient will prevent irreversible complications such as hemiparesis and blindness.…”
Section: Introductionmentioning
confidence: 99%